2019
DOI: 10.1002/ejoc.201901483
|View full text |Cite
|
Sign up to set email alerts
|

Selective Cyanoalkylation and [2+2+2] Annulation of 1,6‐Enynes with Azobis(alkylcarbonitriles) under Mild Conditions

Abstract: In this paper, selective cyanoalkylation and [2+2+2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…After three years, Wei's group used a similar copper-catalyzed approach by modifying the 1,6-enyne substrate to achieve the [2 + 2 + 2] annulation (Scheme 6-2). 15 In this protocol, environmentally friendly H 2 O/EtOAc was used as the co-solvent with significant functional group tolerance. Meanwhile, the reaction temperature was lower and the conditions were milder.…”
Section: [2 + 2 + 2] Annulationmentioning
confidence: 99%
“…After three years, Wei's group used a similar copper-catalyzed approach by modifying the 1,6-enyne substrate to achieve the [2 + 2 + 2] annulation (Scheme 6-2). 15 In this protocol, environmentally friendly H 2 O/EtOAc was used as the co-solvent with significant functional group tolerance. Meanwhile, the reaction temperature was lower and the conditions were milder.…”
Section: [2 + 2 + 2] Annulationmentioning
confidence: 99%
“…At the end of 2019, we reported the use of azobis(alkylcarbonitriles) as a C ‐centered radical source to trigger the cyclization of 1,6‐enynes in the presence of water and ethyl acetate (Scheme 10). [21] Interestingly, the 1,6‐enynes underwent a [2+2+2] annulation in the presence of CuI and AIBN, forming four new chemical bonds. Interestingly, without CuI present, the 1,6‐enynes underwent a unique regioselective cyanoalkylation reaction.…”
Section: Radical Cyclization Of 1n‐enynesmentioning
confidence: 99%
“…The electrophilic halocyclization of alkenes has emerged as an unparalleled platform for the efficient assembling of cyclic compounds via introducing a new halogen group and creating a new ring. In this context, considerable research efforts have been paid to the halocyclization of olefinic 1,3-dicarbonyls and olefinic amides. Nonetheless, from an eco-friendly and practical point of view, these significant achievements are still plagued by some disadvantages, such as the use of catalysts, the necessity of bases or oxidants, and the need for high reaction temperature or toxic organic solvents. In continuation of our research interest in the cyclization reaction, as well as reactions in aqueous media, we recently have found that treatment of olefinic 1,3-dicarbonyls or olefinic amides with halogen sources in aqueous media open to the air at room temperature could realize the synthesis of 2,3-dihydrofurans or benzoxazines (Scheme ). It should be noted that the resulting 2,3-dihydrofurans and benzoxazines are important structural units commonly found in bioactive natural products and pharmaceuticals (Figure ).…”
Section: Introductionmentioning
confidence: 99%